Legitimidades inmanentes: parlamento y esfera pública en Nueva Granada y España - Luengo, Jorge (Anuario de Historia de América Latina, 2019)
This article explores the relationship between parliaments and the public sphere in the Hispanic world during the early nineteenth-century. Scholars tend to interpret the public sphere as a broad communicative space not associated to any particular political institution. In this historiographical context, the role that parliaments played in shaping a new public communicative framework during the revolutionary age needs further attention. By considering legislative bodies in Spain and New Granada between 1810 and 1831, I argue that parliaments function as a body that articulates the public dimension of politics in this period. This interpretation requires considering the inner as well as the outer dimension of the parliamentary institution. While public in the galleries, journalists, and MPs played a fundamental role in shaping the public sphere within the assembly room, they also displayed an intense activity outside parliaments. The space circumventing parliamentary buildings, the role of coffee houses for political discussion, and the centrality of the press will be considered within this analytical framework.